Outcomes of Primary Percutaneous Coronary Intervention at Shahid Gangalal National Heart Centre, Kathmandu, Nepal - Adhikari, Chandra Mani; Bhatta, Yadav Deo; Malla, Rabi; Maskey, Arun; Rajbandari, Rajib; Regmi, Shyam Raj; Sharma, Ranjit; Kansakar, Subodh; Nepal, Himanshu Prasad; Shrestha, Nagman; et al. (Journal of Advances in Internal Medicine, 2013)
Background and Aims- Reperfusion therapy is indicated for patient with acute ST Elevation Myocardial Infarction. Several randomized trials and meta-analyses have shown that Primary Percutaneous Coronary Intervention is better than thrombolysis. Our aim was to determine the outcomes of Primary Percutaneous Coronary Intervention in Shahid Gangalal National Heart Centre, Nepal. Methods- Medical records of 212 Primary Percutaneous Coronary Intervention from March 2007 to March 2012 were retrospectively reviewed. The primary end point was in-hospital mortality and secondary end points were 30 day mortality and long term mortality. Results- In the patients presenting to emergency with acute ST elevation myocardial infarction, inferior wall Myocardial Infarction 64 (30%) was the most common. Single vessel disease 168 (79%) predominated in emergency coronary angiogram. In majority of the patients Right Coronary Artery 103 (48.7%) was the culprit vessel. Cardiogenic shock was present in 28 (13.2%) patients. There were 11 deaths (39.2%) in cardiogenic shock group where as only 5 deaths (2.7%) among 184 non cardiogenic shock patients, resulting in in hospital mortality rate of 7.5%. Among the 196 patients who were successfully discharged from the hospital, 21 patients lost to follow up. There was one death reported within a month, non within three months and four within a year post discharge from the hospital. Conclusions- The result of this study is comparable to the findings elsewhere in the world. Primary Percutaneous Coronary Intervention should be the treatment of choice in treating acute myocardial infarction where the facilities and the expertise are available. Journal of Advances in Internal Medicine 2013;02(01):6-9 DOI: http://dx.doi.org/10.3126/jaim.v2i1.7629